Estimation of the air kerma rate from 137Cs and 134Cs deposited on the ground in the Sakhalin region of Russia after the Fukushima accident - V. P. Ramzaev; A. N. Barkovsky (Радиационная гигиена)
Previous studies conducted by the Federal Service for Surveillance on Consumer Rights Protection and Human Well-Being (Rospotrebnadzor) in Sakhalin Region, Russia in 2011–2012 have shown that soils on the southern Kuril Islands were contaminated with 137Cs and 134Cs due to the accident at the Fukushima-1 NPP. In this study, we evaluated the air kerma rate from 137Cs and 134Cs using earlier published data on the vertical distribution of Fukushima-derived radiocaesium in the soil at grasslands on the islands of Kunashir, Shikotan and Iturup. The air kerma rate due to gamma-rays from pre-Fukushima 137Cs was estimated as well. In the period from May 2011 to September 2012, the air kerma rate due to the fresh fallout of radioactive caesium varied from 0.31 to 0.84 nGy h−1. On average, the contribution of the radiation from Fukushima-derived 134Cs and 137Cs to the total air kerma rate from radioactive cesium was 35% in the fall of 2011 and 25% in the fall of 2012. The mean normalized kerma rate from Fukushima-derived 137Cs was estimated at a level of 1.63 nGy h−1 per kBq m−2 in mid-May 2011, 1.53 nGy h−1 per kBq m−2 in autumn 2011 and 1.45 nGy h−1 per kBq m−2 in autumn 2012. The mean normalized air kerma rate from pre-Fukushima 137Cs at reference undisturbed grasslands was estimated as 0.77 nGy h−1 per kBq m−2. The results of our calculations of the air kerma rate from Fukushima-derived 137Cs were in good agreement with the forecast of the 2013 UNSCEAR model, which was used to estimate the external doses of the Japanese population after the Fukushima accident. For pre-Fukushima 137Cs, the UNSCEAR model underestimated the calculated normalized air kerma rates in Sakhalin Region by approximately 40%. Our calculations showed that, overall, the aboveground biomass of herbaceous plants had practically no effect on the air kerma rate from radioactive cesium contained in the soil. The fallout of 134Cs and 137Cs after the accident at the Fukushima-1 NPP did not lead to any significant increase in the gamma dose rate in the air at grasslands on Kuril Islands. In 2019–2020, the contribution of radiocaesium to the total gamma dose rate in air will not exceed 5%.